The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1152/jn.01061.2005
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Changes in Inputs to Dorsal Y Neurons Accompany VOR Motor Learning

Abstract: . Gain changes in the vestibuloocular reflex (VOR) during visual-vestibular mismatch stimulation serve as a model system for motor learning. The cerebellar flocculus and its target neurons in the brain stem (FTN) are candidates for the storage of these novel VOR gains. We have recently studied the changes in vertical flocculus Purkinje cells after chronic VOR motor learning. Recently we recorded Y neurons (a vertical type of FTNs) after chronic VOR motor learning and compared these records with vertical floccu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…Thus at least a subset of type B cells that have been described in in vitro studies are likely to correspond to the floccular target/eye-head neurons that have previously been described in in vivo studies and have been shown to play an important role in visually induced VOR motor learning in primates (Blazquez et al 2006;Lisberger et al 1994). In alert guinea pig, most VN neurons exhibit a decrease in their head sensitivity in an acute VOR training paradigm (Serafin et al 1999), and recent studies further suggest longer-term changes at the same level underlie memory consolidation required for chronic changes in VOR gain (Kassardjian et al 2005;Shutoh et al 2006).…”
Section: Bridging the Gap: The Relation Between In Vivo And In Vitro mentioning
confidence: 74%
“…Thus at least a subset of type B cells that have been described in in vitro studies are likely to correspond to the floccular target/eye-head neurons that have previously been described in in vivo studies and have been shown to play an important role in visually induced VOR motor learning in primates (Blazquez et al 2006;Lisberger et al 1994). In alert guinea pig, most VN neurons exhibit a decrease in their head sensitivity in an acute VOR training paradigm (Serafin et al 1999), and recent studies further suggest longer-term changes at the same level underlie memory consolidation required for chronic changes in VOR gain (Kassardjian et al 2005;Shutoh et al 2006).…”
Section: Bridging the Gap: The Relation Between In Vivo And In Vitro mentioning
confidence: 74%
“…target neurons (FTN) receive input from both the flocculus and primary vestibular afferents and are thought to be important for VOR adaptation (Lisberger 1994;Blazquez et al 2006). The modulation changes of FTN neurons have corresponded with changes in the VOR gain induced by training with visual-vestibular conflict (Lisberger et al 1994a, b;Galiana and Green 1998), so they seem to be a likely main contributor to unilateral VOR adaptation.…”
Section: Figmentioning
confidence: 99%
“…Prior studies have provided a plausible and testable hypothesis for the neural circuits that mediate the VOR and the sites of cellular changes that cause learning in the VOR (Blazquez et al 2006;Lisberger 1994). The basic circuit is illustrated in Fig.…”
Section: Introductionmentioning
confidence: 99%